A lightweight privacy preservation authentication protocol for IoMT using ECC based blind signature - Kalpana Samal; Shanta Kumari Sunanda; Debasish Jena; Srikanta Patnaik (International Journal of Engineering Business Management)
In the Internet of Medical Things (IoMT), medical devices are connected to the Internet of Things (IoT), allowing better tailored healthcare, faster hospital treatments, more affordable medical solutions, and more patient comfort. The most serious threat to the safety and confidentiality of patient’s medical records is the possibility of attacks on the IoMT environment. In order to address these problems, researchers have proposed several approaches and methodologies. None of these protocols presents a low-computing-overhead method that combines authentication with privacy preservation. This research proposes a protocol for secure authentication of IoMT devices while protecting user privacy. The proposed approach ensures the confidentiality of the IoMT devices connected to the patient’s body while communicating. In addition, the proposed protocol is validated using the widely recognized formal validation tool Automated Validation of Internet Security Protocols and Applications (AVISPA). The suggested protocol resolves existing protocols’ vulnerabilities and is resistant to many well-known security issues. Compared with existing protocols that use public cryptosystems, such ElGamal and RSA, the suggested protocol stands out due to its smaller key size and reduced computational overhead. A comparison with the well-known protocols revealed that the combined method for “lightweight authentication and privacy preservation” is computationally 5 to 6 times more efficient. However, this research has significant real-world implications from various social, economic, and business viewpoints, both locally and globally.